Synthesis of jatropha biolubricant using sodium methoxide as catalyst - Gunam Resul, Mohamad Faiz Mukhtar (2012)
Initially, jatropha methyl ester (JME) was synthesized from extracted jatropha crude oil (JCO) and methanol via transesterification, using sodium hydroxide (NaOH) as catalyst. JME produced, was later reacted with a type of polyol, trimethylolpropane (TMP) to produce jatropha biolubricant, a jatropha based triester, via transesterification using sodium methoxide (NaOCH3) as catalyst. The produced jatropha biolubricant was analyzed by using gas chromatography (GC), differential scanning calorimetry (DSC), pour point test, wear test, viscosity test and biodegradability. The optimum condition to synthesize jatropha biolubricant were as follows; reaction temperature of 150 °C, reactant molar ratio of 3.5:1 and catalyst loading of 0.8% (wt/wt). The kinetic of reaction was studied by varying the operating temperature from 120°C to 200°C, indicating a second order reaction with overall reaction constant found at 3.175 x 10-1 (% wt/wt.min.°C)-1. The thermal-oxidative stability was observed at Ton, 325°C, with the improvement of 56% from the JCO’s thermaloxidative stability which is at 205°C. Physical test on the viscosity index (VI) of the jatropha biolubricant, which was calculated at 183, revealed that the viscosity of the oil does not significantly change upon the variation of temperature. The improvement of pour point from 8°C of JCO to -6°C of jatropha biolubricant justified the chemical modification applied in this research. Furthermore, wear test shows a slightly better improvement of jatropha biolubricant over JCO whereby from the four-ball test, the average scar diameter for jatropha biolubricant was 0.33mm compared to 0.36mm for JCO. In terms of environmental friendliness, the biodegradability test shows that jatropha biolubricant was able to degrade more than 60% as required to be labeled as biodegradable material. Overall, the chemical modification was able to improve the utilization of jatropha based lubricant and resulting in improvements to the chemical and physical properties studied.